Defining the cardiac surgical learning curve: a longitudinal cumulative analysis of a surgeon’s experience and performance monitoring in the first decade of practice - Shantel Chang; Ian Smith; Christopher Cole (Journal of Cardiothoracic Surgery)
Abstract Background Individual surgeons’ learning curves are a crucial factor impacting patient outcomes. While many studies investigate procedure-specific learning curves, very few carried out a longitudinal analysis of individual cardiac surgeons over the course of their career. Given the evolving landscape of cardiac surgery with the introduction of transcatheter and robotic procedures, a contemporary evaluation of the cardiac surgical learning curve is justified and a method of personal performance monitoring is proposed in this study. Methods A retrospective study of 1578 consecutive patients of a cardiac surgeon over ten years was undertaken. Risk adjustment was based on Euroscore. Cumulative risk adjusted morbidity (CRAM) charts of operative mortality, return to theatre and length of stay were constructed. Secondary endpoints included postoperative stroke and deep sternal wound infection. Change-point detection was applied to investigate temporal trends and identify when a significant change in outcome occurred. Multivariate analysis was performed to assess the influence of patient and system factors on operative mortality. Results Patient average risk profile was highest in the later years of practice. Cardiopulmonary bypass time remained stable from 86.5 to 92 min across the decade. The frequency of redo operations increased from 4.07% in the first two years of practice to 9.29% in the last two years. The proportion of aortic surgery increased from 6.98 to 10.58% of total cases. There was a significantly reduced operative mortality signalled at case 1220 with the change point identified around case 970. Conclusion This prompts training colleges to consider application of sequential performance monitoring in surgical training programs, to confirm the progress of trainees and identify early evolving patterns that suggest support is required or milestones are being achieved.